Selection of Selected Flight Attendants Using MCDM-AHP and ELECTRE Method - Akmaludin, Akmaludin; Schaduw, Frans Edward; Purwanto, Heru; Hartati, Tri; Sumbaryadi, Achmad (Politeknik Ganesha Medan, 2019)
The number of business interests nowadays, many people use flight services to reach distant areas and must be traveled by very complex flight services. Such conditions have resulted in a large number of airlines requiring flight attendants to service their passengers on the plane. So that the right method is needed to carry out the selection process for flight attendants, the ELECTRE method is one solution that can be done for the flight attendant's selection process. The results obtained from the selection process of flight attendants without a score, because they have used the elimination process through threshold concordance and threshold discordance as follows, out of nine candidates for flight attendants who have passed the selection are flight attendants-3, flight attendants-6 and flight attendants-7, while others are not acceptable. So that through the results of the selection that has been done with the collaboratin AHP and ELECTRE method, by seeing the results obtained from aggregate matrices dominant.